Factors Influence on Dietary Intake and Practices of Adolescent Girls Aged 15-19 in Rural Area Central Java - Zahroh Shaluhiyah; Ratih Indraswari; Aditya Kusumawati (Amerta Nutrition, 2021)
Background: Dietary habits formed during adolescence have been shown to track into adulthood. Establishing healthy eating behaviours among adolescents, therefore, has both short- and long-term health benefits..Objectives: This study aims to identify dietary habits among adolescent girls aged 15-19 in rural area and its influence factorsMethod: This is a quantitative study with cross-sectional approach, involved 93 adolescent girls aged 15-19 in Jatipurwo village who were selected randomly. Data was collected by enumerators using structure questionnaires that has been validated in other village before.  Univariate, bivariate using Chi-Square and multivariate (logistic regression) were employed to analyze data.Results: The eating behavior of adolescent girls were categorized as unhealthy and unbalanced diet. It was shown with insufficient level of energy including low adequacy of carbohydrate, protein and fat. The average height of adolescents was 155 cm. Most adolescents have LILA less than 23.5cm. As Low socioeconomic family income tends to have eating habits with low nutritional value both in quantity and quality as well as food variations. Lack of food availability at the family level makes teens have poor diet. It is recommended that the need for increased food security at the family level and provide awareness to adolescents about healthy eating.